A Study of Classroom Practices on the Impact of In-Service Training Programme at Secondary Level - Pareek, Ram Babu; Sharma, R.K.; Nainawat, A.K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
It is very essential for any Nation to focus with new developments in the field of education. To keep in this view, the most vital part in Teacher Education has to improve both pre-service as well as in-service training will be put together as under umbrella. The present study was attempted to observe the in-service training programme for teachers at secondary education level. This study was joint collaboration with Ministry of Human Resource Development (MHRD) and National Council of Educational Research and Training (NCERT) taken as a Programme Advisory Committee (PAC) under Rastriya Madyamic Shiksha Abhiyan (RMSA) for classroom observation and to explore the changes in classroom practices of secondary schools as a result of such training. A multi-stage sampling was used for selection of districts and schools. The study was undertaken with the purpose of establishing benchmark on the classroom process in different contexts of secondary education in Uttar Pradesh (UP) State. The main objective of the study was to assess effectiveness/impact of in-service training for secondary school teachers. The instruments of the study were information sheet, observation schedule, Focused Group Discussion and Questionnaire. The analysis of data has been done both quantitative as well as qualitative. Findings revealed that majority of teachers (81.04 percent) have not under gone in-service training programmes. The results indicated that the classes are highly classroom oriented and there is a need to orient the teachers to take the children outside of the classroom wherever possible. The results also indicated that there is a need to reduce teacher talk and increase the time for interaction with the students, performing group work and assessment of learning for improving learner performance.